Automated Validation Framework for Microservice Architectures - Huzaini , Mohd (Journal of Research in Science and Engineering, 2025)
This study aims to provide a comprehensive analysis of microservices testing automation strategies and tools. The research includes a systematic review of existing literature along with practical implementation approaches. The study examines the theoretical foundations of microservices testing, including architecture peculiarities and testing challenges. It then explores various automation strategies, from unit testing to end-to-end testing, with a focus on contract and performance testing. The analysis of testing tools covers frameworks for different testing levels and their integration into CI/CD (Continuous Integration and Continuous Delivery) pipelines. The research presents practical implementation examples, including test environment architecture and code samples. The findings highlight the importance of a balanced testing approach, reproducible test environments, and the continuous optimization of testing processes. The study contributes to the field by offering a holistic view of microservices testing automation, addressing the unique challenges of distributed systems, and providing insights for practitioners and researchers in software quality assurance.